Effect of fuel cost on the price of desalination water: a case for renewables - Kalogirou, Soteris A. (My University, 2001)
Cyprus suffers from droughts, which sometimes continue for a number of consecutive years and create serious water shortage problems. In the past the efforts of the Government were towards the erection of dams, but the water management system dependence on the weather was not alleviated. The first reverse osmosis desalination plant was erected 5 years ago. Three more plants, one of the same capacity and two with half, are planned in the near future. The Government believes that with the completion of all these plants, the water shortage problem will be solved permanently. As Cyprus has no fossil fuel resources, it relies entirely on fuel imports for its energy needs. It is estimated that 25% of the price of the desalinated water is attributed to the energy cost. This is a parameter that should never be underestimated as all plants are powered with electricity, which is produced entirely from imported fuels. The only natural resource of Cyprus is solar energy, which is abundantly available. It is thus sensible to develop desalination systems which can even partly be powered from solar energy systems, either through a combination of photovoltaics and the existing or planned reverse osmosis systems or from a combination of solar thermal and distillation evaporators. The first one is considered in this paper. These are all mature technologies and thus the financial risk from their implementation is minimum. The added benefit from the adoption of renewable energy sources, besides the issues related to environmental protection, is that they reduce dependency on imported fuels.
Keywords: Energy cost; Renewable energy sources; Photovoltaics